Efektifitas Ketentuan tentang Roya pada Jaminan Fidusia Kendaraan - Lia Trizza F.A (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This study aims to determine and analyze the effectiveness of the application of the rules regarding Notification of Elimination of Fiduciary Guarantee Certificates and their sanctions as stipulated in Article 16 paragraph (2) and Article 17 paragraph (2) of Government Regulation Number 21 of 2015 concerning Procedures for Registration of Fiduciary Guarantees and Fees for Making Deeds. Fiduciary Guarantee, as well as Article 19 paragraph (2) and Article 20 paragraph (2) of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 25 of 2021 concerning Registration of Fiduciary Guarantee, Change of Fiduciary Guarantee Certificate and Elimination of Fiduciary Guarantee Certificate, especially regarding the abolition of Fiduciary Guarantee with a motor vehicle guarantee object. This research is normative legal research using a statutory approach, a case approach, and a conceptual approach. The results of the study show that there are several ways to eliminate fiduciary guarantees based on the provisions of Article 16 paragraph (1) PP Number 21 of 2015 and Article 19 paragraph (1) of the Regulation of the Minister of Law and Human Rights Number 25 of 2021. namely because of the elimination of debt guaranteed by fiduciary rights, release of fiduciary security rights by fiduciary recipients, or destruction of objects that are objects of fiduciary guarantees. If the fiduciary guarantee has been canceled, then 14 (fourteen) days from the date of the fiduciary guarantee must be notified to the Minister. Based on the notification of elimination, the fiduciary guarantee is declared to have been confiscated or removed from the fiduciary guarantee list and a certificate of elimination will be issued stating that the relevant Fiduciary Guarantee Certificate is no longer valid.